Características nutricionales y antioxidantes de la fruta curuba larga (Passiflora mollissima Bailey) (2014)
ABSTRACT: banana passion fruit is a tropical fruit whose nutritional value and bioactive compounds are little known and have not been studied enough. Objective: based on the nutritional and antioxidant characteristics of banana passion fruit we show the nutritional value and the impact to human health. Methodology: characteristics of fruit and production were described. Proximal composition of the fruit was analyzed. Micronutrients were known by scientific references related to banana passion fruit. Antioxidant capacity was analyzed by DPPH, FRAP and ORAC methods. Results: this is a source of vitamins A, C and niacin, minerals such as potassium, phosphorus, magnesium, sodium, chlorine, iron; provides moderate amounts of carbohydrates and calories. The content of total carotenoids, phenols and flavonoids was 118,8 mg βcarotene 460,1 mg galic acid galic and, 1.907,6 mg catechine/100 g respectively. The DPPH, FRAP and ORAC value was 60.843,1 µmol, 8.520,3 µmol and, 20.754,9 µmol trolox equivalents/100 g dehydrated fruit respectively. Conclusion: people in general and the food industry should take advantange of the nutritional and antioxidant value of banana passion fruit as well as raw material to improve the productive chain.